From cartel party to traditional membership organisation: the organisational evolution of Fianna Fáil. Issue 1 (2nd January 2017) - Bolleyer, Nicole; Weeks, Liam
ABSTRACT: This paper examines patterns of intra-organisational evolution and reform of Fianna Fáil as a party organisation before and after the 2011 Dáil election, widely considered an 'earthquake election' that fundamentally undermined Fianna Fáil's status as the dominant party in the Irish party system. Electoral losses had triggered reform in Fianna Fáil prior to 2011, but such reforms tended to be minor, as the party expected its opposition status to be temporary. This orientation changed after 2011, as the party's very foundation seemed threatened, having suffered a historic decline of its electoral support and membership. We argue that the post-2011 re-orientation can be usefully characterised as a movement away from organisational characteristics associated with the 'cartel model of party organisation' towards characteristics echoing more 'traditional mass party structures', an organisational model less dependent on state resources, and more able to generate loyalty through organisational means. Whether the 2011 reforms will lead to lasting change is likely to depend on whether, and if so how quickly, Fianna Fáil can reclaim its position as the major party of government.